2022
DOI: 10.1111/ctr.14768
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life and psychological indicators of thriving 15–19 years after heart or lung transplantation

Abstract: Background: Survival into the second decade after cardiothoracic transplantation (CTX) is no longer uncommon. Few data exist on any health-related quality of life (HRQOL) impairments survivors face, or whether they may even experience positive psychological outcomes indicative of "thriving" (e.g., personal growth). We provide such data in a long-term survivor cohort. Methods: Among 304 patients prospectively studied across the first 2 years post-CTX, we re-interviewed patients ≥15 years post-CTX. We (a) examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…This finding has also been supported in some reviews ( 42 , 43 ). Nevertheless, a few studies showed some patients were at a low level of QOL after LTx, which were likely due to the interaction of various factors including physical, psychological, and social factors ( 11 , 44 ). Our study mainly focused on identifying the LTx patients at risk for a low QOL using LPA, and determined the multidimensional predictors associated with the specific profile membership of QOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding has also been supported in some reviews ( 42 , 43 ). Nevertheless, a few studies showed some patients were at a low level of QOL after LTx, which were likely due to the interaction of various factors including physical, psychological, and social factors ( 11 , 44 ). Our study mainly focused on identifying the LTx patients at risk for a low QOL using LPA, and determined the multidimensional predictors associated with the specific profile membership of QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, those outcomes were negatively associated with QOL, creating a vicious cycle that ultimately may lead to a decreased life expectancy ( 10 ). Hence, ongoing QOL evaluation is required, and it is necessary to identify patients with poor QOL to provide supportive care ( 11 ).…”
Section: Introductionmentioning
confidence: 99%